The Military in Politics : Changing Patterns in Brazil - Stepan, Alfred C. (Book collections on Project MUSE., 1971)
The nature of the military institution in Brazil, its relations with civilian governments up to 1964, and its use of power since the coup of that year are examined by Alfred Stepan. Throughout his study, while looking at the Brazilian experience, he tests and reformulates implicit and explicit models, propositions, and middle-range hypotheses in the literature of civil-military relations and in political development theory. Professor Stepan's analysis suggests that many of the expectations and hypotheses held by theoreticians and policymakers about the capabilities of the military in moderni.